Atomic Clocks: The Search for Variation of Fundamental Constants with Clocks (Ann. Phys. 5/2019). Issue 5 (9th May 2019) - Safronova, Marianna S.
Abstract : If the fundamental constants, such as the fine‐structure constant α, are space‐time dependent so are atomic spectra and the clock frequencies. As discussed in article number1800364 by Marianna S. Safronova, the extraordinary improvement of atomic clocks has enabled testing the constancy of the fundamental constants at a very high level of precision. A future nuclear 229 Th clock may have much larger sensitivity to the variation of α than atomic clocks.